The great revivalists in American religion, 1740 - 1944: the careers and theology of Jonathan Edwards, Charles Finney, Dwight Moody, Billy Sunday and Aimee Semple McPherson - Cooper, William H. (McFarland, 2010)
"This work shows how revivalism moved from the Edwardian emphasis on the amazing works of God, as the Puritans would have put it, to the "new methods" of Charles Finney and revival as the reasonable works of man as befits Jacksonian democracy. Later, D.L. Moody concentrated on methodology to such a degree that revivals became big business. "--Provided by publisher